2017
DOI: 10.1111/pcmr.12657
|View full text |Cite
|
Sign up to set email alerts
|

Suppression of MAPK signaling in BRAF‐activated PTEN‐deficient melanoma by blocking β‐catenin signaling in cancer‐associated fibroblasts

Abstract: Cancer-associated fibroblasts (CAFs) in the tumor microenvironment have been associated with formation of a dynamic and optimized niche for tumor cells to grow and evade cell death induced by therapeutic agents. We recently reported that ablation of β-catenin expression in stromal fibroblasts and CAFs disrupted their biological activities in in vitro studies and in an in vivo B16F10 mouse melanoma model. Here, we show that the development of a BRAF-activated PTEN-deficient mouse melanoma was significantly supp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 60 publications
(92 reference statements)
0
11
0
Order By: Relevance
“…10 Further studies showed that targeted ablation of β-catenin in murine stromal fibroblasts had opposite biological effects on melanoma development depending on the timing of β-catenin ablation. 10,14 Despite these interesting results, the mechanisms by which β-catenin regulates the biological properties of human stromal fibroblasts and their interactions with melanoma cells and the ECM remain largely unknown. To address this question, we used inducible lentiviral shRNAs (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…10 Further studies showed that targeted ablation of β-catenin in murine stromal fibroblasts had opposite biological effects on melanoma development depending on the timing of β-catenin ablation. 10,14 Despite these interesting results, the mechanisms by which β-catenin regulates the biological properties of human stromal fibroblasts and their interactions with melanoma cells and the ECM remain largely unknown. To address this question, we used inducible lentiviral shRNAs (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…To understand whether β-catenin is related to YAP nuclear localization in melanoma-associated fibroblasts, we collected tumor tissues from mice bearing Braf V600E ; Pten lox5 - Fb or Braf V600E ; Pten lox5 -bcat/Fb melanoma 14 for double staining using an anti-YAP antibody and an anti-α-SMA antibody. A majority of α-SMA-positive fibroblasts in control Braf V600E ; Pten lox5 - Fb melanomas showed red fluorescent staining of YAP (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations